2021
DOI: 10.1108/ijphm-11-2021-0116
|View full text |Cite
|
Sign up to set email alerts
|

The effects of task environment and organizational agility on perceived managerial discretion and strategy implementation in a pharmaceutical company

Abstract: Purpose This study aims to investigate the relationship between task environment, organizational agility, perceived managerial discretion and strategy implementation on unit performance. Design/methodology/approach Based on the literature review, a structural model was developed. A 74-item questionnaire was circulated among middle managers in sales and marketing. The data collection method used purposive sampling. A total of 228 valid responses were obtained. This study was conducted in a leading pharmaceuti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(8 citation statements)
references
References 58 publications
(85 reference statements)
1
6
0
Order By: Relevance
“…An organization's capability to operate in turbulent and uncertain conditions will lead managers at every level to perceive that they have broad latitude. This finding is in line with studies that have found that OA is an internal factor that affects PMD [ 2 , 5 ].…”
Section: Discussionsupporting
confidence: 93%
See 4 more Smart Citations
“…An organization's capability to operate in turbulent and uncertain conditions will lead managers at every level to perceive that they have broad latitude. This finding is in line with studies that have found that OA is an internal factor that affects PMD [ 2 , 5 ].…”
Section: Discussionsupporting
confidence: 93%
“…Managers have freedom of choice when establishing their work in a given situation [ 17 , 29 ]. They have discretion in achieving organizational goals [ 5 , 6 , [30] , [31] , [32] ]. With developed discretion, managers have a wider range of options to make decisions and, hence, greater latitude [ 33 , 34 ].…”
Section: Literature Review and Hypothesis Developmentmentioning
confidence: 99%
See 3 more Smart Citations